2019
DOI: 10.1111/jce.14052
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation after catheter ablation of atrial fibrillation and the associated risk of thromboembolic events and intracranial hemorrhage: A systematic review and meta‐analysis

Abstract: Aims: We sought to examine whether continuing oral anticoagulation (OAC) after catheter ablation (CA) for atrial fibrillation (AF) is associated with improved outcomes. OAC reduces morbidity and mortality in patients with AF. However, the continuation of OAC following the blanking period of CA is controversial due to conflicting published data.Methods: A systematic review of Medline, Cochrane, and Embase was performed for studies comparing patients who were continued on OAC (ON-OAC) vs those in which OAC was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“… 7 and Romero et al . 8 In the first, anticoagulant therapy was not effective unlike what was shown in the second. A possible explanation of this dissonance is probably to be found in the different basic thromboembolic risk profile of the patients included in the analysis.…”
Section: Anticoagulant Therapymentioning
confidence: 97%
“… 7 and Romero et al . 8 In the first, anticoagulant therapy was not effective unlike what was shown in the second. A possible explanation of this dissonance is probably to be found in the different basic thromboembolic risk profile of the patients included in the analysis.…”
Section: Anticoagulant Therapymentioning
confidence: 97%
“…No significant benefit from continued OAC was observed in the low‐risk cohort. Intra cranial hemorrhage was significantly higher in the OAC group (risk ratio 5.78, 95% CI, 1.33‐25.08, P = .02) …”
Section: Summary Of Three Meta‐analysis Examining Te Risk Following Amentioning
confidence: 98%
“…In this issue of the Journal, Romero et al present a systematic review and meta‐analysis of OAC after catheter ablation of AF . They found that OAC continuation was associated with a significant decrease in the risk of thromboembolic events (TE) in the high‐risk cohort (CHA 2 DS 2 VASC ≥ 2; risk ratio 0.41, 95% Confidence Interval [CI] 0.21‐0.82, P = .01).…”
Section: Summary Of Three Meta‐analysis Examining Te Risk Following Amentioning
confidence: 99%
See 1 more Smart Citation
“…Catheter ablation (CA) for AF has steadily advanced over the past two decades, with improvements in success rates. Although current practice guidelines recommend OAC based on established indices of stroke risk such as the CHA 2 DS 2 ‐VASc score, 1 regardless of the perceived success of ablation, 2 a practice of safely discontinuing OAC following CA in selected populations has been reported in several observational studies 3–5 …”
Section: Introductionmentioning
confidence: 99%